2021
DOI: 10.1186/s12909-021-02649-0
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the general medicine in-training examination score between community-based hospitals and university hospitals: a cross-sectional study based on 15,188 Japanese resident physicians

Abstract: Background The general medicine in-training examination (GM-ITE) is designed to objectively evaluate the postgraduate clinical competencies (PGY) 1 and 2 residents in Japan. Although the total GM-ITE scores tended to be lower in PGY-1 and PGY-2 residents in university hospitals than those in community-based hospitals, the most divergent areas of essential clinical competencies have not yet been revealed. Methods We conducted a nationwide, multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…It covers four areas of basic clinical knowledge, including ‘medical interview and professionalism,’ ‘symptomatology and clinical reasoning,’ ‘physical examination and clinical procedures,’ and ‘disease knowledge’. 14 , 15 These areas correlate with the PGME objectives as established by the Japanese Ministry of Health, Labor and Welfare. The Japan Institute for Advancement of Medical Education Program (JAMEP), a nonprofit organization, developed the GM‐ITE as an objective evaluation of residents' basic clinical knowledge.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…It covers four areas of basic clinical knowledge, including ‘medical interview and professionalism,’ ‘symptomatology and clinical reasoning,’ ‘physical examination and clinical procedures,’ and ‘disease knowledge’. 14 , 15 These areas correlate with the PGME objectives as established by the Japanese Ministry of Health, Labor and Welfare. The Japan Institute for Advancement of Medical Education Program (JAMEP), a nonprofit organization, developed the GM‐ITE as an objective evaluation of residents' basic clinical knowledge.…”
Section: Methodsmentioning
confidence: 84%
“…The general medicine in‐training examination (GM‐ITE) is a computer‐based test consisting of 80 multiple‐choice questions. It covers four areas of basic clinical knowledge, including ‘medical interview and professionalism,’ ‘symptomatology and clinical reasoning,’ ‘physical examination and clinical procedures,’ and ‘disease knowledge’ 14,15 . These areas correlate with the PGME objectives as established by the Japanese Ministry of Health, Labor and Welfare.…”
Section: Methodsmentioning
confidence: 99%
“…Reportedly, junior residents working for community hospitals score higher than those working for university hospitals on the General Medicine In-Training Examination (GM-ITE), 32 which assesses junior residents’ medical knowledge, 33 indicating that junior residents can learn more from clinical cases in early phases 32 because community hospitals primarily provide care to as many local residents as possible. In addition, factors related to the GM-ITE high score were rotation in the general medicine department, 34 more admitted patients to care for, 35 and receiving clinical training in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that early practical training in clinical rotation programs for postgraduate trainees may be associated with improved medical knowledge, improved attitudes toward patients, confidence in delivering medical care, and improved clinical performance. [27][28][29][30][31] Reportedly, junior residents working for community hospitals score higher than those working for university hospitals on the General Medicine In-Training Examination (GM-ITE), 32 which assesses junior residents' medical knowledge, 33 indicating that junior residents can learn more from clinical cases in early phases 32 because community hospitals primarily provide care to as many local residents as possible. In addition, factors related to the GM-ITE high score were rotation in the general medicine department, 34 more admitted patients to care for, 35 and receiving clinical training in rural areas.…”
mentioning
confidence: 99%
“…Similar to previous studies regarding the GM-ITE, resident physicians from university hospitals had lower GM-ITE scores in this study. 37 The low PUD index group had a lower proportion of university hospitals, which may be a confounding factor. Third, the resident physicians' baseline clinical skills were not assessed.…”
Section: Limitationsmentioning
confidence: 96%